2011
DOI: 10.3892/mmr.2011.523
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of polymorphisms in Rad51 and Xrcc3 on breast cancer risk and chromosomal radiosensitivity

Abstract: Abstract. Enhanced in vitro chromosomal radiosensitivity (CRS) has been proposed as a marker for low-penetrance gene mutations predisposing to breast cancer (BC). Since the double strand break (DSB) is the most detrimental form of DNA damage induced by ionizing radiation, it is possible that mutations in genes encoding proteins involved in DSB repair affect breast cancer risk. The purpose of the present study was to examine whether five single nucleotide polymorphisms (SNPs) in Rad51 and Xrcc3 (rs1801320, rs18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…Several other studies and meta-analyses have confirmed an association between the XRCC3 Thr241Met polymorphism and it is suggested that this may be involved in modifying the risk of cancer [ 40 ]. Interestingly some studies show that it may have a protective effect [ 4 , 41 ], while still others failed to show any association with lung cancer in the Danish [ 42 ], breast cancer in the Polish [ 3 ], Belgian [ 43 ], and Jordanian populations [ 37 ], and ovarian cancer in a meta-analysis including Caucasian, Asian, and African populations [ 44 ]. During our analysis, no differences were found in the frequency of this SNPs when the patients were separated into groups on the basis of the age of diagnosis, tumor grade, and receptor (ER, PR, and HER2) status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies and meta-analyses have confirmed an association between the XRCC3 Thr241Met polymorphism and it is suggested that this may be involved in modifying the risk of cancer [ 40 ]. Interestingly some studies show that it may have a protective effect [ 4 , 41 ], while still others failed to show any association with lung cancer in the Danish [ 42 ], breast cancer in the Polish [ 3 ], Belgian [ 43 ], and Jordanian populations [ 37 ], and ovarian cancer in a meta-analysis including Caucasian, Asian, and African populations [ 44 ]. During our analysis, no differences were found in the frequency of this SNPs when the patients were separated into groups on the basis of the age of diagnosis, tumor grade, and receptor (ER, PR, and HER2) status.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated this mutation in different cancers and the results are contradictory even in patients suffering from the same type of cancer in different populations, as shown in Table 7 . A study from the British population showed that rs1799796 decreases the risk of breast cancer [ 2 ] while another study from Belgium reported an increased risk associated with this SNP in BRCA1 and BRCA2 carriers [ 43 ]. More recently, a significant association with ovarian cancer was confirmed in a meta-analysis involving Caucasian, Asian, and African populations [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of hypersensitivity to ionizing radiation are still unclear, but is estimated that 70% of hypersensitivity cases are due to genetic variants ( Turesson et al , 1996 ). As mentioned above, mutations in the ATM gene are associated with extreme hypersensitivity to ionizing radiation ( Masuda and Kamiya, 2012 ), and polymorphisms in genes like XRCC3 and RAD51 increase the risk of radiosensitivity ( Vral et al , 2011 ). These genes are also implicated in breast cancer.…”
Section: Ionizing Radiation-associated Dna Damage Radiotherapy and Mmentioning
confidence: 99%
“…MSH2 is one of the genes involved in DNA mismatch repair and located on chromosome 2 at 2p21. It has also been shown that polymorphism in Rad51 a gene located on chromosome 15 at 15q15.1 and involved in double strand break repair, can enhance cancer risk and in vitro chromosomal radiosensitivity [4,5]. It has also been postulated that genetic polymorphism of androgen receptor may act as a risk-modifier for BRCA2-associated breast cancers [36].…”
Section: Discussionmentioning
confidence: 99%